Pengaruh Deep Neck Flexor Exercise terhadap Neck Pain Non-Specific pada Penjahit - Salwa Maylani; Nugroho, Fendy; Yoni Rustiana (UI Scholars Hub, 2025)
Background: tailors tend to bow for a long time which results in excessive activation of the postural muscles in maintaining the position of the neck which causes weakness, decreased activity, and muscle imbalance which results in pain in the neck area. In overcoming these disorders, the intervention that can be given is deep neck flexor exercise. Objective: to determine the effect of deep neck flexor exercise on non-specific neck pain in tailors. Methods: this study used an experimental one group pre and post test with control design which was carried out in May-July 2024 at PT. Iskandar Indah Printing Textile with 30 subjects. The subject collection technique was carried out randomly by drawing lottery numbers. Group I was given an intervention in the form of deep neck flexor exercise and group II was given education about ergonomic positions for tailors. The study was conducted for 6 weeks with 2 meetings each week. Pain measurements using QVAS were carried out at the beginning and end of the study. Results: based on the results of statistical tests before and after treatment, group I obtained a p value = 0.001 (p 0.05) which indicates that there is no difference in QVAS before and after treatment in the control group. The results of the hypothesis test after treatment in groups I and II obtained a p value = 0.001 (p<0.05) which indicates that there is a difference in influence. Conclusion: giving deep neck flexor exercise can reduce pain in tailors who suffer from non specific neck pain.